Application of Landfill Leachate Improves Wheat Nutrition and Yield but Has Minor Effects on Soil Properties. Issue 1 (1st January 2017) - Kuwano, Biana H.; Nogueira, Marco A.; Santos, Cristiane A.; Fagotti, Dáfila S.L.; Santos, Michele B.; Lescano, Luís E.A.M.; Andrade, Diva S.; Barbosa, Graziela M.C.; Tavares‐Filho, João
Abstract : Landfill leachates, which are potential pollutants, may also carry significant amounts of nutrients that can be recycled by plants. We assessed the nutritional status and yield of wheat ( Triticum aestivum L.) and properties of a Rhodic Kandiudult soil (depths of 0–10, 10–20, 20–40, and 40–60 cm) after 11 applications of landfill leachate over 4 yr. In the last application, wheat received 0, 32.7, 65.4, 98.1, or 130.8 m 3 ha −1 (875 mg L −1 of nitrogen, N) of leachate and a positive control (90 kg ha −1 of N as urea) 15 d after sowing. Urea increased nitrate (>160 mg kg −1 ) in the topsoil (down to 40 cm), whereas landfill leachate increased nitrate (>60 mg kg −1 ) only at 40 to 60 cm with the highest dose, suggesting leaching. Urea‐treated soil had less negative ΔpH, which might have led to greater retention of nitrate in the topsoil. Sodium (0.02–0.26 cmolc Na kg −1 ), potassium (0.18–0.82 cmolc K kg −1 ), and electrical conductivity (0.05–0.14 dS m −1 ) all increased with leachate dosage. Treatments did not affect resistance to penetration and clay dispersion. Basal respiration increased with leachate dosage, whereas dehydrogenase activity decreased, suggesting effects on soil microbial metabolism. Microbial biomass and soil enzyme activities were not affected by addition of leachate. Nitrogen nutrition (15.1–22.7 g N kg −1 in flag leaves) and grain yield (1381–2378 kg grain ha −1 ) increased with leachate dosage so that the highest dose gave results similar to those for urea‐treated plants (2563 kg grain ha −1 ). Landfill leachate showed strong potential as source of N for wheat but caused none, or transient, effects on soil properties. However, nitrate from leachate was more leachable than nitrate from urea. Core Ideas: Agricultural soil received 11 applications of landfill leachate over four years. Assessments up to 60 cm showed no major concerns on soil attributes. Nitrate from leachate was more leachable than nitrate from mineral fertilizer. Wheat plants benefited from nitrogen in the leachate for nutrition and grain yield.